Artropoda yang berasosiasi pada ekosistem tanaman lada - Iwa Mara Trisawa; I Wayan Laba; Warsi Rahmat Atmadja (Perhimpunan Entomologi Indonesia, 2005)
Association of Arthropod on Pepper Plant Ecosystem. Ecosystem management of pepper between cover crops, Arachis pintoii, cropping system with corn, soybean and limited weeding. The objectives of this research was to find out biodiversity of arthropod on the paper ecosystem. This experiment was conducted in Lampung since May to September 2002. They are divided 5 treatments they are paper with A. pintoii, pepper with corn, pepper with soybean, pepper with limited weeding and control. The randomize blok design was used 44 kind of arthropods. The status of arthropod are: fitofag (47.73%), omnivorus (6.82%), natural enemies (34.09%) and pollination (11.36%). Distribution of each species was various at each treatment, between 26-34 species. The lowest population was found on pepper with corn, while on the highest population were occurred on the pepper with A. pintoii and control. The insect population of Acrididae, Tetrigidae, Grylidae (Orthroptera), Blattidae, Drosophillidae and Farmicidae always higher than an other insect. In this research were found 10 ordo of arthropod. Hymenoptera (Formicidae) and Araneida are dominant of arthropod and distributed at all treatment. Arthropod at pepper plant was the most abundant at pepper plan with A. pintoii. In the pepper standing plant it were only found three other, they are Hymenoptera, Araneida and Hemiptera. Beside at pepper plant and pepper standing plant, some of arthropod was found associated with A. pintoii, corn, soybean weed. Other of Orthoptera mainly grasshopper was dominating at all of plant.